Heat pipes as perspective base elements of heat recovery in heat supply and ventilating systems - Matveev Andrey; Zelentsov Danila; Louks Alexander (MATEC Web of Conferences, 2017)
Thermotechnical characteristics of heat pipes are considered as high-efficient heat-transfer devices, which can provide energy-saving technologies for heat supply and ventilating systems and for different branches of industry. Thermotechnical and working (”performance capability”) characteristics of heat pipes are investigated. By ”performance capability” of heat pipes and heat-transfer devices on heat pipes we mean the system state, where it can perform set functions and keep parameter values (thermal power, conductivity, thermal resistance, heat-transfer coefficient, temperature level and differential, etc.) within the regulations of standardized specifications. The article presents theoretical and experimental methods of «gaslock» length determination on noncondensable gases during long-lasting tests of ammonia heat pipes made of aluminum shape АS – КRА 7.5 – R1 (alloy АD – 31). The paper gives results of research of thermotechnical characteristics of heat pipes in horizontal and vertical states (separate and as a set part) while using different systems of thermal insulation. The obtained results of thermotechnical and resource tests show the advantages of ammonia heat pipes as basic elements for heat exchanger design in heating and ventilation systems.